Comparison of satisfaction with post-operative pain management and level of functional interferance in addicted and non-addicted patients - Hamid Reza Koohestani; Nayereh Baghcheghi; Korosh Rezaei (Guilan University of Medical Sciences, 2014)
Introduction: Postoperative pain relief in addicted patients compared with non-addicted patients is often more challenging and they usually suffer from inadequate postoperative pain relief. Objective: The purpose of this study was to compare satisfaction with postoperative pain management in addicted and non-addicted patients and level of pain interference with their functions. Methods: In this analytic cross sectional study, 105 addicted and 105 non addicted patients admitted to the surgical ward of Saveh Modares hospital in 2012 were selected. Two study groups were compared as regard to intensity of pain, satisfaction with postoperative pain management and level of pain interference with functions. Data collection instrument included a 4 section questionnaire that the first part covered patients' demographics, second part contained universal pain assessment tool, the third part included items on level of pain interference with their functions (usual functions, walking, emotions, sleep and relations with others) and fourth part was related to assessment of satisfaction with post-operative pain. Questionnaire was used after determining its validity and reliability. The data were statistically analyzed utilizing descriptive statistics and Pearson corelational T test and chi square test analytic. Results: The majority of subjects (57.14%) in addicted group were dissatisfied from pain control after surgery, while 14.28 percent of non-addicted patients were dissatisfied with pain control post-operatively and this difference was significant (P=0.001). The results showed that postoperative pain interfered with functions in the areas of mood, sleep and relationships with others which was significantly different between two groups (P=0.01). Conclusion: The results indicated that special attention should be paid to concept of pain relief in addicted patients, especially acute pain such as pain after surgery and their rights as patients must be considered and respected.